Mathematical modelling of the recombination capacity of system of enzymes acting on - Sarmin, Nor Haniza; Ahmad, Tahir; Huyop, Fahrul Zaman; Shamsuddin, Siti Mariyam; Fong , Wan Heng (Faculty of Science, 2007)
This research initiates the connection between formal language theory and the study of informational macromolecules. The modelling of a biological splicing system has been done mathematically through formal language theory, which is a branch of applied group theory and theoretical computer science. The accuracy of how a splicing works has been verified through the corresponding biological splicing system. In this research, different kinds of languages that result from the action of restriction enzymes on strings of DNA molecules have been studied. Examples of strictly locally testable languages are given. Besides, some theorems related to different combination of restriction enzymes in a strictly locally testable language are presented. A language is local if every string of a certain length is a constant relative to it. Some theorems related to concepts of constant and local are also given. A maximal firm subword of a word is discussed, where automata concept is used to illustrate the simple splicing system. This research also gives few actual molecular considerations for the molecules that will arise from a given initial sets of strings using some chosen restriction enzymes. This research has brought together the communities of mathematical scientists and bio-molecular scientists since each of these sciences can make a contribution to the other. The most specific benefit of this research is the application of mathematical analysis of questions of which DNA bio-molecules can potentially arise in a test tube from the action of specific sets of enzymes acting on the specific sets of DNA molecules.